The antifungal susceptibility of Candida albicans isolated from HIV/AIDS patients - Sri Rezeki; Siti Aliyah Pradono; Gus Permana Subita; Yeva Rosana; S. Sunnati; Basri A. Gani (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: Candida albicans was found to be dominant in patients with human immunodeficiency virus / acquired immunodeficiency syndrome (HIV/AIDS). The antifungals fluconazole, ketoconazole, and nystatin were used as oral candidiasis therapy for HIV/AIDS, each of which has differing susceptibility in oral candidiasis therapy. Purpose: The present study aimed to evaluate the susceptibility and antifungal resistance to oral C. albicans in HIV/AIDS patients. Methods: The subjects followed the universal precaution principles. Oral Candida species were isolated from the saliva of 98 HIV/AIDS subjects. Identification of Candida species was carried out by the mycobiotic agar of API 20 C Aux system. Susceptibility and resistance antifungal tests on the Candida species were performed using a Fungus ATB Kit. Results: Candida albicans was the most dominant species found from 98 subjects (95%). The rest were other Candida species. There are 41 subjects (42%) with a history of oral candidiasis, and 57 subjects (58%) without. The history of those who used antifungals were: nystatin = 60 subjects (61%), fluconazole = 39 subjects (40%), and ketoconazole = two subjects (2%). These antifungals have a susceptibility above 80% against C. albicans, except the nystatin group (79%) (p>0.05; 0.628), but fluconazole has a strong correlation (r=0.820) to susceptibility, susceptibility-dependent dose, and resistance. Conclusion: Candida albicans was dominant in the saliva of HIV/AIDS patients. This fungus was effectively treated by fluconazole, ketoconazole and nystatin. These antifungals had a high susceptibility at ≤ 8 μg/mL to C. albicans.